Sliding mode and PID control of a structural system against earthquake - Guclu, R (PERGAMON-ELSEVIER SCIENCE LTD, 2006)
In this study, a non-chattering robust sliding mode controller (SMC) and a proportional integral derivative (PID) Controller are separately designed for an active seismic control device considering a multi-degree-of-freedom structural system against earthquakes. Since the PID control method can be applied easily and is widely known, it has an important place in control applications. But this method is insensitive to parameter changes. The advantage of an SMC is its robustness and ability to handle the non-linear behaviour of the system. The simulated system has four degrees of freedom. A structural system was simulated against the ground motion of the Marmara earthquake (M-w = 7.4) in Turkey on August 17th, 1999. The ground motion acts on the base. Both PID and sliding mode controllers are designed to suppress the building vibrations. Since the main effect of an earthquake occurs on the first floor, the controller is placed under it. At the end of the study, the time history of the first and top floor displacements, frequency responses of both the uncontrolled and controlled structures and control voltages are presented and the results are discussed. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: SMC and PID control; structural system; earthquake; vibration; Computer Science; Mathematics